Are tree plantations promoting homogenization of mammal assemblages between regions with contrasting environments?. (15th February 2021) - Iezzi, María Eugenia; De Angelo, Carlos; Cruz, Paula; Varela, Diego; Di Bitetti, Mario S.
Abstract: Aim: The expansion of agriculture is promoting the loss of natural environments and their biotic homogenization. We aimed at understanding whether the replacement of forests and grasslands by tree plantations leads to biotic homogenization of mammal assemblages of two contrasting Neotropical ecoregions or if dispersal or environmental limitations keep their original assemblages clearly differentiated. Location: Argentina, Upper Paraná Atlantic Forest, Southern Cone Mesopotamian Savannas and Iberá marshes. Taxon: Mammals. Methods: We conducted two camera‐trap surveys, deploying 184 camera‐trap stations in continuous forest, fragmented forest and pine plantations in the Atlantic Forest, and 234 in grassland, fragmented forest and pine plantations in the Mesopotamian Savannas. We evaluated the similarity of the assemblages among the environments and regions, generating all possible pairwise comparisons using three similarity indices: Sørensen (species identity), Horn (common species) and Morisita‐Horn (dominant species). Using variation partitioning diagrams and redundancy analysis, we evaluated the spatial structure of mammal assemblages and the influence of environmental variables. Results: There was a greater similarity in species identity between different environments within each region than between similar environments in different regions. Common and dominant mammal assemblages of tree plantations tended to be similar between regions and were different from assemblages of the natural environments within the same region. Fragmented forest assemblages were very similar among regions. Assemblages were spatially structured but most of the variation between regions was explained by the environmental variables. Main conclusions: Each region has a distinct pool of species, which is partially explained by environmental factors, such as the differential representation of native environments in the landscape. However, an expansion of tree plantations and forest fragmentation in the Atlantic Forest could lead to biotic homogenization between regions due to an increase in the abundance of generalist species.